Quit Smoking Experts’ Opinions toward Quality and Results of Quit Smoking Methods Provided in Tobacco Cessation Services Centers in Iran - Heydari, Gholamreza (Int J Prev Med, 2015)
BACKGROUND: One of the core responsibilities of health system is to treat tobacco dependence. This treatment includes different methods such as simple medical consultation, medication, and telephone counseling. To assess physicians’ opinions towards quality and result of different quit smoking methods provided in tobacco cessation services centers in Iran. METHODS: In this cross-sectional and descriptive study, random sampling of all quit centers at country level was used to obtain a representative sample size of 100 physicians. Physicians completed a self-administered questionnaire which contained 10 questions regarding the quality, cost, effect, side effects, and the results of quitting methods using a 5-point Likert-type scale. Percentages, frequencies, mean, T-test, and variance analyses were computed for all study variables. RESULTS: Most experts preferred to use combination quit smoking methods and then Nicotine Replacement Therapy (NRT) with 26 and 23, respectively. The least used methods were quit line and some methods without medication with 3 cases. The method which gained the maximum scores were telephone consultation, acupuncture, Willpower, Champix, combined method, and Interactive Voice Response (IVR) with the mean of 23.3, 23, 22.5, 22, 21.7 and 21.3, respectively. The minimum scores were related to e-cigarette, some methods without medication, and non-NRT medication with the mean of 12.3, 15.8 and 16.2, respectively. There were no significant differences in the mean of scores based on different cities (P = 0.256). Analysis of variance in mean scores showed significant differences in the means scores of different methods (P < 0.000). CONCLUSIONS: According to physicians acupuncture, personal methods and Champix are the most effective methods and these methods could be much more feasible and cost effective than other methods.